2013
DOI: 10.1139/cjpp-2013-0095
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren, exendin-4, and insulin: their impact on endothelin receptor subtype(s) regulation/binding in type 1 diabetic rat hearts

Abstract: This study focuses on the impact of aliskiren and (or) glucagon-like peptide-1 analogue on the binding affinity/regulation of endothelin-1 (ET-1) to its receptor subtypes A (ETAR) and B (ETBR) at the level of the coronary endothelium and the cardiomyocytes in a type-1 diabetic rat model. Seven groups were used: (i) normal rats, (ii) rats with induced diabetes, (iii) rats with induced diabetes that were treated with insulin, (iv) rats with induced diabetes that were treated with exendin-4, (v) rats with induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
0
1
Order By: Relevance
“…who demonstrated that FMD was reduced by % 45 in patients with T1DM without any complications compared to controls (24). Endothelin-1 is a marker of ED and plays role in angiogenesis, fibrosis, inflammation and acts as a vasopressor agent causing HT (25). In our study there wasn't any significant difference in sET1 level between the diabetic subgroups and the control group.…”
Section: Biochemical and Clinic Markers Of Ed In T1dmcontrasting
confidence: 43%
“…who demonstrated that FMD was reduced by % 45 in patients with T1DM without any complications compared to controls (24). Endothelin-1 is a marker of ED and plays role in angiogenesis, fibrosis, inflammation and acts as a vasopressor agent causing HT (25). In our study there wasn't any significant difference in sET1 level between the diabetic subgroups and the control group.…”
Section: Biochemical and Clinic Markers Of Ed In T1dmcontrasting
confidence: 43%